ChemInform Abstract: Sesquiterpenes from the Rhizomes of Cyperus rotundus and Their Potential to Inhibit LPS‐Induced Nitric Oxide Production. Issue 44 (14th October 2013) - Kim, Su Jung; Ryu, Byeol; Kim, Ha‐Yeong; Yang, Yeong‐In; Ham, Jungyeob; Choi, Jung‐Hye; Jang, Dae Sik
Abstract Two new (I) and seven known sesquiterpenes are isolated and evaluated for their title activity.